Controlled Osteogenic Differentiation of Mouse Mesenchymal Stem Cells by Tetracycline-Controlled Transcriptional Activation of Amelogenin. - Fangfang Wang; Hiroko Okawa; Yuya Kamano; Kunimichi Niibe; Hiroki Kayashima; Thanaphum Osathanon; Prasit Pavasant; Makio Saeki; Hirofumi Yatani; Hiroshi Egusa (PLoS ONE)
Regenerative dental therapies for bone tissues rely on efficient targeting of endogenous and transplanted mesenchymal stem cells (MSCs) to guide bone formation. Amelogenin is the primary component of Emdogain, which is used to regenerate periodontal defects; however, the mechanisms underlying the therapeutic effects on alveolar bone remain unclear. The tetracycline (Tet)-dependent transcriptional regulatory system is a good candidate to investigate distinct roles of genes of interest during stem cell differentiation. Here, we investigated amelogenin-dependent regulation of osteogenesis in MSCs by establishing a Tet-controlled transcriptional activation system. Clonal mouse bone marrow-derived MSCs were lentivirally transduced with the Tet repressor (TetR) expression vector followed by drug selection to obtain MSCs constitutively expressing TetR (MSCs-TetR). Expression vectors that contained the Tet operator and amelogenin-coding (Amelx) cDNA fragments were constructed using the Gateway system and lentivirally introduced into MSCs-TetR to generate a Tet regulation system in MSCs (MSCs-TetR/Amelx). MSCs-TetR/Amelx significantly overexpressed the Amelx gene and protein in the presence of the tetracycline derivative doxycycline. Concomitant expression of osterix, bone sialoprotein (BSP), osteopontin, and osteocalcin was modulated by addition or removal of doxycycline under osteogenic guidance. During osteogenic induction, MSCs-TetR/Amelx treated with doxycycline showed significantly increased gene expression of osterix, type I collagen, BSP, and osteocalcin in addition to increased alkaline phosphatase activity and mineralized nodule formation. Enhanced extracellular matrix calcification was observed when forced Amelx expression commenced at the early stage but not at the intermediate or late stages of osteogenesis. These results suggest that a Tet-controlled Amelx gene regulation system for mouse MSCs was successfully established, in which transcriptional activation of Amelx was associated with enhanced osteogenic differentiation, especially in the early stage of biomineralization.